Spatiotemporal characteristics and the national variations of borderland use change in Laos within the geopolinomical context - Wang, Yi; Xiao, Chiwei (Frontiers in Forests and Global Change, 2023)
Laos, the only landlocked country in Mainland Southeast Asia (MSEA), has established over forty geopolinomical mechanisms with its neighbouring countries that have led to significant land use change (LUC) in the border areas. However, spatial characteristics and national differences of LUC in Laos's border areas remain unknown. Using land-use products during 1985-2020 and GIS spatial analysis, the results indicate that: (1) LUC in Laos's border is manifested in the deforestation due to the expansion of construction land and cropland. While changes of construction land changes range from stable to accelerated expansion, cropland shows the opposite trend. (2) With strengthened border cooperation, differences between LUC in Laos and its neighbouring countries have decreased since 1985. (3) Cropland and construction land on Laos-China and Laos-Thailand borders show obvious bordering characteristics with increasing land-use homogeneity in near-border areas. In contrast, Laos-Vietnam, Laos-Cambodia, and Laos-Myanmar borders show display the opposite trend. (4) Port areas (e.g., Boten-Mohan port) driven by geopolinomical relations have drastic LUC,but there are huge differences among them. This study provides a database for quantitative research on interaction between geopolinomical relations and border LUC to promote border geography, including impact and response. This is a provisional file, not the final typeset article and forefront for exerting geopolinomical influence and implementing geopolinomical strategy, national border areas are experiencing rapid and widespread land-use change (LUC). According to statistics from the European Space Agency's Global Land Cover Data Survey, border areas, which occupy approximately one-twelfth of the global land area, have disproportionately contributed to approximately one-third of global LUC since 1990(Xiao et al., 2021). Therefore, it is critical to understand the spatio-temporal characteristics and regional differences of border LUC to facilitate cooperation among neighbouring countries and formulate effective land policies.Currently, analyses of LUC from different perspectives have been conducted, such as analysis of landscape patterns (Tscharntke et al., 2005), spatio-temporal variations (Zhai et al., 2022), drivers